Feeding the City Work and Food Culture of the Mumbai Dabbawalas - Roncaglia, Sara (Open Book Publishers, 2013)
Every day in Mumbai 5,000 dabbawalas (literally translated as "those who carry boxes") distribute a staggering 200,000 home-cooked lunchboxes to the city's workers and students. Giving employment and status to thousands of largely illiterate villagers from Mumbai's hinterland, this co-operative has been in operation since the late nineteenth century. It provides one of the most efficient delivery networks in the world: only one lunch in six million goes astray. Feeding the City is an ethnographic study of the fascinating inner workings of Mumbai's dabbawalas. Cultural anthropologist Sara Roncaglia explains how they cater to the various dietary requirements of a diverse and increasingly global city, where the preparation and consumption of food is pervaded with religious and cultural significance. Developing the idea of "gastrosemantics" - a language with which to discuss the broader implications of cooking and eating - Roncaglia's study helps us to rethink our relationship to food at a local and global level. The publication of this book is financed by the generous support of interested readers and organisations, who made donations using the crowd-funding website unglue.it